Analisis Standarisasi Sarana dan Prasarana Futsal di Kedungwuni Kabupaten Pekalongan (Universitas Negeri Semarang, 2022)
Based on the research background, the focus of the problem in the study is the Standardization Analysis of the Futsal Field in Kedungwuni District, Pekalongan Regency. The purpose of this research is to know the standard size, futsal field facilities in Kedungwuni Subdistrict, Pekalongan Regency. The method used in this research is a combination method. Combined method is a research method that combines quantitative methods and qualitative methods. The model in this study adopts a combination research method with a concurrent embeded model, in which qualitative research is the primary method and quantitative research methods are the secondary method. The subjects of this study were the owners / guards of the field and fusal players. The research data collection technique uses the method of observation, interviews, documentation, and the preparation of data collection tools. Data analysis techniques include: data collection, data reduction, data presentation, conclusion drawing and verification, data credibility testing. The results of the research carried out the percentage of field standards include: Annas Futsal 66.6%, Mercy Bless Futsal 61.1%, and HW Muhammadiyah Pekajangan Sport Center 50%. which is good enough. This explains that the size of the field and facilities in Kedungwuni Subdistrict, Pekalongan Regency are good enough and can be used. The conclusion from the analysis of Futsal field standards in Kedungwuni District, Pekalongan Regency is quite standard. Based on the research results and suggestions that the researcher can convey, namely paying more attention to field standards both size and dot mark, as well as maintenance of facilities for the convenience of visitors.